Retrieval of a Fractured Marathon Microcatheter Entrapped in Onyx Using a Novel Stentriever-Assisted Technique. Issue 4 (14th October 2022) - Jackson, Lachlan; Ma, Alice; Faulder, Kenneth
Abstract : BACKGROUND AND IMPORTANCE: Endovascular embolization using Onyx has been a major advancement in the treatment of cerebrovascular malformations. Microcatheter entrapment in Onyx is a procedural complication which can pose a thromboembolic risk to patients. There have been 4 retrieval techniques for intact microcatheters entrapped in Onyx previously described in the literature, which are summarized in this report. We present the first case using a novel stentriever-assisted technique to successfully and safely retrieve a fractured microcatheter entrapped in Onyx. CLINICAL PRESENTATION: An adult patient with a Cognard IIa + b dural arteriovenous fistula (dAVF) underwent Onyx embolization. The microcatheter became entrapped and fractured while initially attempting removal. A stentriever was used off label to capture the fractured microcatheter and then a larger caliber microcatheter was railroaded over it. Retrieval of the fractured microcatheter by the stentriever was then facilitated by counter traction on the Onyx cast using the larger microcatheter. CONCLUSION: This novel stentriever-assisted technique is a safe and effective rescue maneuver for retrieving a fractured microcatheter trapped in Onyx during embolization of dAVF. There is a need for further research and development of novel devices for retrieval of entrapped microcatheters.